Gambaran Pola Makan Pada Anak Usia Sekolah di SDN Pondok Kelapa 06 Jakarta Timur - Azizah, Restiana Nur; Rizana, Anna (Universitas Malahayati, 2023)
ABSTRAK Children's diet really needs serious treatment because it affects the optimal status of growth, development, and brain intelligence for children. During the growth period and feeding needs to be regulated according to the recommended nutritional adequacy rate. Children who lack daily physical activity can cause their bodies to expend less energy. One of the keys to fulfilling children's nutritional needs is to introduce them to various types of food. If a child is too picky about food (picky eater) then the child will be at risk of experiencing nutritional deficiencies. A healthy diet to support children's growth and development must be given varied intake from an early age, pay attention to food hygiene, and be in accordance with the child's physical activity so that the child's ideal weight is achieved. Eating habits is a term used to describe habits and behaviors related to dietary regulation. This type of stimulating food needs to be considered so as not to damage the gastric mucosal lining. To know if there is an overview of eating patterns in elementary school-age children. This study uses an observational method with a quantitative analytic approach with a cross sectional study design that aims to analyze the risk factors and effects at the same time. Where the measurement of the variable that is examined is the description of eating patterns in elementary school-age children. Based on the results of filling out the questionnaire conducted by students in grades IV and V at Pondok Kelapa 06 Sdn, East Jakarta, from all 60 respondents, the results obtained were the gender (demographic data) of 38 female respondents (63.33%) and 22 male respondents (36.37%). From the results of the univariate analysis, it was found that out of the 60 respondents who were examined, there were 45 respondents (75%) who had a good diet and 15 people (25%) who had a bad diet. There is an overview of eating patterns in children at Pondok Kelapa 06 Sdn. A description of the types of food that are often consumed by school-age children at Pondok Kelapa 06 elementary school, East Jakarta who consume carbohydrate sources such as rice as many as 38 people (64%) and noodles as many as 40 people (67%) , who consumed animal side dishes such as chicken eggs as many as 43 people (72%), who consumed vegetable side dishes such as tofu as many as 43 people (72%), who consumed vegetables such as carrots, bean sprouts and cucumbers as many as 23 people (38%) and those who consumed fruit like watermelon as many as 29 people (48%). Researchers provide advice to all students of Pondok Kelapa 06 Elementary School to pay more attention to eating patterns, eating habits and types of food that are healthy and clean. Because a good diet is expected to avoid the risk of malnutrition or other diseases that can affect the growth and development of school-age children. a. Education about healthy snacks Provide education to elementary school-age children about the criteria for snacks that are healthy and safe for health by providing open pockets or leaflets showing the characteristics of unhealthy foods in terms of color, shape, aroma and texture. b. Education about balanced nutrition Providing education about balanced nutrition through pictorial media such as